Counterrevolutionary Crimes in Judicial Practice of Simbirsk Governorate Revolutionary Tribunal in 1918-1920 - R. A. Mukhamedov (Научный диалог, 2019)
The article is devoted to the analysis of counterrevolutionary crimes in 1918-1920 on the basis of the cases accepted for consideration by Simbirsk Governorate Revolutionary Tribunal. The authors introduce previously unavailable archival documents into scientific circulation. Details are given to such aspects of the topic as the jurisprudence of the emergency justice system in the fight against the counter-revolution, as well as the necessary conditions for the final verdict against the accused. The analysis of the verdicts issued by the emergency justice body is carried out. Attention is paid to examples of acts committed by citizens in 1918-1920 and recognized as counterrevolutionary. Statistical data on the activity of the emergency justice body of Simbirsk governorate are given. The novelty of the research is seen in the fact that for the first time a large layer of previously classified unpublished archival documents was introduced into scientific circulation. The main conclusions of the study are the following key provisions: firstly, Simbirsk Governorate Revolutionary Tribunal was an effective tool of the Bolshevik regime, and secondly, the emergency justice body in 1918-1920 paid close attention to the investigation of counter-revolutionary cases, which amounted to about 29 %, and thirdly, in sentencing Tribunal staff were guided by the class principle.